Joint Statement (DZK, DGRh, DDG) on the Tuberculosis Risk with Treatment Using Novel Non-TNF-Alpha Biologicals - Diel, R.; Schaberg, T.; Nienhaus, A.; Otto-Knapp, R.; Kneitz, C.; Krause, A.; Fabri, M.; Mrowietz, U.; Bauer, T.; Häcker, B. (Pneumologie, 2021)
Background While the risk of tuberculosis (TB) reactivation is adequately documented in relation to TNF-alpha inhibitors (TNFi), the question of what the tuberculosis risk is for newer, non-TNF biologics (non-TNFi) has not been thoroughly addressed.Methods We conducted a systematic review of randomized phase 2 and phase 3 studies, and long-term extensions of same, published through March 2019. Of interest was information pertaining to screening and treating of latent tuberculosis (LTBI) in association with the use of 12 particular non-TNFi. Only rituximab was excluded. We searched MEDLINE and the ClinicalTrial.gov database for any and all candidate studies meeting these criteria.Results 677 citations were retrieved; 127 studies comprising a total of 34,293 patients who received non-TNFi were eligible for evaluation. Only 80 out of the 127 studies, or 63 %, captured active TB (or at least opportunistic diseases) as potential outcomes and 25 TB cases were reported. More than two thirds of publications (86/127, 68 %) mentioned LTBI screening prior to inclusion of study participants in the respective trial, whereas in only 4 studies LTBI screening was explicitly considered redundant. In 21 studies, patients with LTBI were generally excluded from the trials and in 42 out of the 127 trials, or 33 %, latently infected patients were reported to receive preventive therapy (PT) at least 3 weeks prior to non-TNFi treatment.Conclusions The lack of information in many non-TNFi studies on the number of patients with LTBI who were either excluded prior to participating or had been offered PT hampers assessment of the actual TB risk when applying the novel biologics. Therefore, in case of insufficient information about drugs or drug classes, the existing recommendations of the German Central Committee against Tuberculosis should be applied in the same way as is done prior to administering TNFi. Well designed, long-term “real world” register studies on TB progression risk in relation to individual substances for IGRA-positive cases without prior or concomitant PT may help to reduce selection bias and to achieve valid conclusions in the future.